Recent Status and Research & Development in the Carbon Capture, Utilization and Storage Technology - Mahidin Mahidin; Farid Mulana; Adisalamun adisalamun; A.A. Reza; M. F. Dhedia; A. Annisak; Halimatussakdiah Halimatussakdiah; Abdul Hadi (Journal of Applied Technology, 2023)
The recently rapid extension and expansion of the industrial and energy sector has increased the number of carbon dioxide (CO2) in environment. Consequently, many concerns have been studied about the prevention of global warming and the achievement of climate mitigation strategy.  In this paper, the current situation of many aspects of carbon capture, utilization and storage (CCUS) technologies were concisely reviewed and discussed. The CCUS technology, using CO2 separation/capture, storage, utilisation, and sequestration processes, is currently considered as the most proactive method to prevent the emission of CO2 to the atmosphere and mitigate climate change and global warming. In this paper, the source of CO2 production and which country that produce its carbon dioxide were discussed and also reviewed type of technologies could be adopted to capture of those CO2 with its any advantages and disadvantages. In order to employ those technologies as a cost-effective technology for the reduction of CO2 emissions from the use of fossil fuels, research and development in its related processes and materials should put in a highest priority.